The Relationship of Pregnant Women's Knowledge of Pregnancy Emergency Signs with Compliance in Antenatal Care (ANC) Examinations in the Working Area of the Sipatana Health Center - Sintiawati Irianto; Ika Wulansari; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
Adolescence is a transition period that is susceptible to various emotional and psychological changes, so it requires the support of a healthy family environment. One of the factors that affect adolescent mental health is parental parenting. Toxic parenting is a form of negative parenting characterized by excessive control, criticism, and a lack of emotional support, which can affect the psychological well-being of adolescents. This study aims to find out the relationship between toxic parenting and mental health in adolescents. The research instruments were in the form of a toxic parenting questionnaire and a Strength and Difficulties Questionnaire (SDQ). The results showed that most adolescents experienced a moderate level of toxic parenting (65.9%), while a weak level was (34.1%). Adolescent mental health conditions are mostly in the borderline (48.8%) category, followed by the abnormal (36.6%) and normal (14.6%) categories. The results of the Chi-square test showed a p-value = 0.002 (< 0.05), which indicates that there is a significant relationship between toxic parenting and adolescent mental health. In conclusion, the higher the level of toxic parenting, the greater the risk of mental health disorders. It is recommended that parents implement positive parenting that is oriented towards emotional support and open communication to support adolescent mental health.